Forceps delivery audit poster. (7th June 2011) - Hussain, N; Baxter, J; Modder, J; Tahir, N
Abstract : Aims: To audit cases where there was a forceps delivery and establish whether the rate could be reduced. This followed an increase in the rate of forceps delivery in UCLH from 3% in 2006 to 8% in 2008. Materials and methods: 84 case notes of women who had forceps delivery between January 2008 and June 2008 were identified, collected from the electronic maternity record and analysed. The audit tool was created from the RCOG and UCLH guidelines. Standards audited: 1. Active pushing can be delayed for up to 2 h in the second stage of labour. 2. Instrumental vaginal deliveries should be classified using a standard classification system that takes station on vaginal examination and fifth palpable abdominally into account. 3. There were recognised indications present prior to forceps delivery (e.g., suspected fetal compromise, failure to progress). Results: In 9.5% of cases of women who had forceps delivery, the guideline has not been followed. The forceps delivery rate might be reduced if the 9.5% of women who had a forceps delivery without any emergency indications had laboured longer. This should include careful monitoring of the progress of the second stage of labour and the use of the partogram.